Comparative evaluation of pain perception with a new needle-free system and dental needle method in children: a randomized clinical trial - Halenur Altan (BMC, 2021)
Abstract Background Pain control during dental procedures is one of the most important topics related to behavior management in children. This study aims to compare the pain perception associated with a needle-free system (Comfort-In™) and the dental needle method during filling and pulpotomy treatments in children. Methods The study included teeth that required treatment (pulpotomy or filling treatment) in 56 patients aged 4 to 11 years with no systemic problems or history of allergy. Patients were randomly divided into the needle-free system group (filling treatment, n = 13; pulpotomy, n = 15) and dental needle method group (filling treatment, n = 14; pulpotomy, n = 14). For pulpotomy and filling treatment performed with 0.3 mL anesthesia, the active ingredient of which is 2% lidocaine and 1/80000 epinephrine. The patients’ behavior before the procedure was evaluated by a pediatric dentist using the Frankl Behavior Scale. The pain intensity was assessed Immediately after injection (induction), during treatment (treatment), and at the end of the treatment (post treatment) by the Wong-Baker Faces Pain Scale. Results The median (IQR-InterQuartile Range) induction pain value was 6[3-8] and 2[0-4] in dental needle method and needle-free system respectively, p < 0.001). In filling and pulpotomy treatment group, no difference between the needle and needle-free group for treatment and post-treatment pain values. Conclusions For pulpotomy and filling treatment, needle-free system performed with 0.3 mL anesthesia was found as effective as infiltrative anesthesia with a dental needle method. Trial registration ClinicalTrials.gov , NCT04653974 . Registered 4 December 2020 – Retrospectively registered.